Optimization and Measurements on the Double Mini-Betay Lattice in the TPS Storage Ring. (November 2019) - Chiu, M S; Chen, C H; Liu, Y C; Tseng, F H; Kuo, C C; Tsai, H J; Chen, J Y; Hu, K H; Chiu, P C; Liao, C Y; Cheng, Y S; Lee, T Y; et al.
Abstract: The Taiwan Photon Source (TPS) is capable of operating in multi-bunch and single-bunch mode. To operate in a hybrid mode as requested by users, we developed a lattice with chromaticities of 0.8/2 (ξx /ξy ) to provide higher single bunch currents. Beam dynamics simulations and lattice characterizations including dynamic aperture, frequency map analysis, tune shift with energy, tune shift with amplitude, and betatron coupling will be discussed in this report.